Universal monsters: dracula (2023) ebook - Tynion IV, James (Universal Monsters: Dracula (2023), 2024)
"The Dracula comic I've wanted all my life." __—ROBERT KIRKMAN (INVINCIBLE, THE WALKING DEAD)  THE DEPARTMENT OF TRUTH creators JAMES TYNION IV (W0RLDTR33, Something is Killing the Children) and MARTIN SIMMONDS re-team to tell a new tale of the monster who started it all!?  When Dr. John Seward admits a strange new patient named Renfield into his asylum, the madman tells stories of a demon who has taken residence next door. But as Dr. Seward attempts to apply logic to the impossible...his daughter falls under the spell of the twisted Count Dracula! ?  Featuring a Direct Market Exclusive cover by STEPHANIE PEPPER that will only be printed once.  Collects UNIVERSAL MONSTERS: DRACULA #1-4